Penerapan prinsip DIR/Floortime Meningkatkan Kemampuan Memusatkan Atensi pada Anak dengan ADHD - Ratih Larasati; Lia M. Boediman; Mita Aswanti (Jurnal Ilmu Perilaku, 2017)
Developmental, Individual Differences, Relationship-Based approach (DIR/Floortime) is one of the available interventions focused on increasing the quality of caregiver-child interaction. This study is aimed at investigating the effectiveness of DIR/Floortime to increase the ability to sustain attention on a 4 year-old child with Early Onset Attention-Deficit/Hyperactivity Disorder (ADHD). This is a qualitative research involving two participants, a boy diagnosed with ADHD, and the mother of the boy. This research utilized observation and interview in gathering the data, accompanying the use of observation log for duration of attention and frequency of distractedness specifically designed for this research, Functional Emotional Assessment Scale (FEAS), questionnaire and interview guideline: Observing Child’s Biological Challenge (OCBC), and Sensory Processing – Motor Planning Questionnaire (SPMPQ). The result of this study indicated that the application of DIR/Floortime principles is effective in increasing the ability to sustain attention on a 4 year-old child with Early Onset ADHD, along with the increase of the functional emotional development of both mother and child as shown with the increase of attention span, the decrease of frequency of distractibility, and score increase in the Functional Emotional Assessment Scale (FEAS).